Ketersediaan Sarana dan Prasarana Pendidikan Jasmani di SMP/MTS Swasta Se-Kecamatan Bulakamba Kabupaten Brebes - Ragil Susyanto; Rekha Ratri Julianti; Setio Nugroho (Jurnal Ilmiah Wahana Pendidikan, 2021)
Facilities and infrastructure is a problem that exists in education, it is necessary to reform in education, we must seek facilities that are in accordance with the needs from the field to the problem of tools or physical education practice facilities that help the teaching and learning process. A fact that often occurs in schools, including in private junior high schools throughout the Bulakamba District, Brebes Regency, that the use of facilities and infrastructure has not been fulfilled or adequate, thus making an obstacle for physical education teachers in providing material for teaching and learning activities. This study aims to determine the availability of physical education facilities and infrastructure in Private Junior High Schools/Mts in Bulakamba District, Brebes District. Descriptive research is a research approach that intends to be able to find out the condition of the situation or event that is currently happening, and the results of which will need to be presented in the form of a research report. Qualitative research is research that produces findings that cannot be achieved by using statistical procedures or by quantitative means. The data collection technique used in this research is observation. The subject of this research is the physical education facilities and infrastructure in private junior high schools in Bulakamba district, Brebes Regency which has 3 junior high schools. The data collection technique is triangulation (combined), the data analysis is inductive/qualitative, and the results of qualitative research emphasize meaning rather than generalization. The research design used in this study is phenomenology. Based on the results of the research, it can be concluded about "Availability of physical education facilities and infrastructure in private junior high schools/mts in Bulakamba district, Brebes district". For facilities and infrastructure at junior high schools in Bulakamba sub-district, they are included in the "Not Good" category, based on the data taken at each school in accordance with the research reference norms.